Kajian Yuridis Penerapan Turut Tergugat dalam Gugatan Wanprestasi dan Sita Jaminan - Victor Ary Subekti; Rocky Marbun (Syntax Corporation, 2023)
In civil law, problems in the legal realm can occur due to someone's actions that harm others, intersecting with the legal realm in the sense of a non-conformity of intent with the purpose in an agreement or agreement. The actions of a person or certain party in an agreement or agreement, which harms other parties are actually regulated in law are also called unlawful acts, while those that harm others due to negligence, negligence, or broken promises are known as defaults or defaults. This study will review the position of the Defendant in a tort lawsuit, which aims to provide an explanation of the legal standing of the Defendant, other than the Plaintiff or Defendant, in a civil case. Although the existence of Defendants in laws and regulations has not been regulated, there have been many legal experts who discuss it and there are also many Supreme Court jurisprudence that can be used as a basis. In compiling this journal, the author uses qualitative research methods by collecting data taken from civil law literature sources so as to produce a summary of explanations that can be used as a reference in proceedings in civil law.